Assessment of Nasal Breathing Function and Tip Definition after the Implementation of the Cephalic Lateral Crural Advancement Flap Technique - Macía, Germán; Ortega, Ana (Facial Plastic Surgery, 2024)
Cephalic trimming of the lower lateral cartilage (LLC) can result in the collapse of the internal and external nasal valves, pinched nose, and alar retraction. The cephalic lateral crural advancement flap (CLCAF) technique is introduced as a method to prevent these complications by avoiding grafts in the LLC. A retrospective study was conducted on 126 open-approach rhinoplasties (82 female and 44 male) employing the CLCAF technique between January 2021 and March 2022. Preoperatively, 20 patients exhibited collapse of the internal nasal valve. CLCAF was performed in all patients following cephalic incision, leaving 7 to 8 mm horizontally and caudally of LLC, and preserving the scroll ligament. The CLCAF was advanced onto the lateral crura to reinforce it and tension the scroll ligament. The Nasal Obstruction Symptom Evaluation (NOSE) scale was used to assess the technique. The average postoperative follow-up period was 14 months. Overall, 114 patients (90.5%) experienced improved nasal breathing on the NOSE scale, and the overall NOSE score significantly decreased from a mean of 30.4 to 14.0 (p < 0.001). A statistically significant reduction in NOSE scores was observed in groups with moderate, severe, and extreme obstruction (p < 0.001), with greater improvement seen in the patients with more severe preoperative nasal breathing obstruction. Postintervention, no patient exhibited collapse of the internal valve, and all patients with preoperative collapse of the internal nasal valve showed an increase of at least 40 points in the NOSE scale. Two patients required revision due to tip asymmetry related to CLCAF. Pinched nose or alar retraction was not observed postoperatively in any patient. The implementation of CLCAF, combined with other techniques, enhances nasal breathing function, prevents the collapse of the internal nasal valve, and leads to optimal nasal tip definition, resulting in a better-shaped and functioning nose.
Keywords: rhinoplasty; aesthetic; ligaments; rotation; surgical flaps